Gestão associada de serviços públicos no Brasil: federalismo cooperativo, administração pública e direitos fundamentais - Melo, Álisson José Maia (2013)
Within the framework of federal entities, especially local ones, agreements for delegating or sharing tasks to perform public services have been frequently made. Based on the Constitutional Amendment No. 19, in 1998, public consortia and cooperation agreements for associated management of public services were institutionalized in the current constitutional order, with the purpose of standardizing legal discipline on those agreements. It seeks to verify to what extent the associated management of public services is an appropriate instrument to ensure the autonomy of federal units and to promote the fundamental rights related to public services. The study of the associated management of public services is preceded by discussions on the criteria for the analysis of the institute, namely the themes related to Brazilian federalism and public services adopted by the 1988 Brazilian Constitution, and after the presentation of the main features of associated management associated, it proceeds to the collation of the institute from those criteria. The methodology adopted involves solely the analysis of publications and documentation, specifically the legislative, and argumentative discussion on the interpretation of this material. From an examination of the associated management of public services systematic, implemented through public consortia and cooperation agreements with the characteristics of Brazilian federalism and public services defined constitutionally, it turns out that the associated management can only be accepted within the national legal framework if the strict version of federalism, with its rigid spheres of competence, is rejected, adopting a more flexible and dynamic federalism, in which it allows the interference of a federal entity to assist in achieving the competence of another entity. It is concluded that the associated management of public services is an institute that shows itself consistent and appropriate to a particular reading of the 1988 Brazilian Constitution, the dynamic and finalistic features, toward the implementation of fundamental rights. Due to these features, it is necessary an argumentative refinement of judicial control when federal conflicts of jurisdiction and the adoption of shared solutions are involved.